Maximal Voluntary Ventilation Should Not Be Estimated From the Forced Expiratory Volume in the First Second in Healthy People and COPD Patients - Otto-Yáñez, Matías; Sarmento da Nóbrega, Antônio José; Torres-Castro, Rodrigo; Araújo, Palomma Russelly Saldanha; Carvalho de Farias, Catharinne Angélica; Dornelas De Andrade, Armele de Fátima; Puppo, Homero; Resqueti, Vanessa Regiane; Fregonezi, Guilherme Augusto de Freitas (Frontiers in Physiology, 2020)
Purpose To evaluate the concordance between the value of the actual maximum voluntary ventilation (MVV) and the estimated value by multiplying the forced expiratory volume in the first second (FEV1) and a different value established in the literature. Methods A retrospective study was conducted with healthy subjects and patients with stable chronic obstructive pulmonary disease (COPD). Eleven prediction formulas MVV were used for the comparison with the MVV values. Agreement between MVV measured and MVV obtained from 5 prediction equations were studied. FEV1 values were used to estimate MVV. Correlation and agreement analysis of the values was performed in two groups using the Pearson test and the Bland-Altman method; these groups were: one group with 207 healthy subjects and the second group with 83 patients diagnosed with COPD, respectively. Results We recruited 207 healthy subjects (105 women, age 47±17 year) and 83 COPD patients (age 66±6 years; 29 GOLD II, 30 GOLD III, 24 GOLD IV) for the study. All prediction equations presented a significant correlation with the MVV value (from 0.38 to 0.86, p<0.05) except for GOLD II subgroup, which had a poor agreement with measured MVV In healthy subjects, the mean difference of the value of bias (and limits of agreement) varied between -3.9% (-32.8 to 24.9%) and 27% (-1.4 to 55.3%). In COPD patients, the mean difference of value of bias (and limits of agreement) varied between -4.4% (-49.4 to 40.6%) and 26.3% (-18.3 to 70.9%). The results were similar in the subgroup analysis. Conclusions The equations to estimate the value of MVV present a good degree of correlation with the real value of MVV, but they also show a poor concordance. For this reason, we should not use the estimated results as a replacement for the real value of MVV.